The Classification of Mathematical Literacy Ability in Cognitive Growth Learning Viewed from Multiple Intelligences - Aprilia Nurul Chasanah (Southeast Asian Mathematics Education Journal, 2021)
This  research aims to determine the quality of the Cognitive Growth mathematical learning model towards mathematical literacy ability and to describe the classification of mathematical literacy ability viewed from the theory of multiple intelligences. This descriptive qualitative study involved 30 eight-grade students with the inclination on each type of multiple intelligence as the research subjects. The data were collected through test, observation, and interviews. The research revealed the following points: (1)the quality of mathematical learning using the Cognitive Growth model was in the good category; (2)mathematical literacy ability in Cognitive Growth learning viewed from multiple intelligences theory can be classified into: verbal-linguistic, logical-mathematical, and fourth-level musical intelligences; third-level visual-spatial intelligences,second-level intrapersonal intelligences, and first-level bodily-kinesthetic, interpersonal, and naturalistic intelligences. Based on these results, this study concludes that the mathematical literacy on different topics compiled based on the indicators of mathematical literacy in cognitive growth learning model has been well improved.